Implementasi Pembelajaran Adaptif Berbasis Teknologi dalam Mengakomodasi Perbedaan Gaya Belajar Siswa SDN 102 Kota Bengkulu - Marisa Rachelia Putri; Arrum Agustina; Wiwinda; Randi (JURNAL ARMADA PENDIDIKAN, 2026)
This study aims to analyze the implementation of technology-based adaptive learning in accommodating differences in student learning styles at SDN 102 Bengkulu City and identify supporting and inhibiting factors. The study used a qualitative approach with a descriptive type. The research subjects consisted of 1 class teacher, 28 fifth-grade students, and 1 principal as a supporting informant. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The results show that technology-based adaptive learning has been implemented gradually through the use of digital media such as learning videos, educational applications, and online platforms. This approach is able to accommodate differences in student learning styles, namely visual, auditory, and kinesthetic, so that the learning process becomes more flexible, interactive, and learner-centered. Supporting factors include the availability of technological devices, school support, and student enthusiasm. Meanwhile, inhibiting factors include limited internet access, unequal distribution of teachers' digital competencies, and limited time in lesson planning. The impact of this learning implementation is seen in increased motivation, engagement, and student learning outcomes, while encouraging the development of critical and creative thinking skills. Thus, technology-based adaptive learning is an effective strategy in improving the quality of education in elementary schools.